A Multidisciplinary Approach to Medieval and Early Modern Land Use: a Case Study from Southeastern Austria. Issue 4 (24th April 2014) - Fazioli, K. Patrick
ABSTRACT This paper presents an integrated multimethod approach to the prospection and reconstruction of medieval and early modern rural landscapes in southeastern Austria (ca. 1100–1700 ce). Pedestrian surface collection, soil phosphorus analysis, and targeted test excavation, along with place‐name and field‐shape data, were used to investigate patterns of settlement, land use and landscape organization. The results from fieldwork revealed an inverse relationship between surface ceramic densities and soil phosphate levels, suggesting different areas of rubbish disposal, habitation and agricultural practices. This case study illustrates both the benefits and challenges of synthesizing archaeological, geochemical and historical lines of evidence in the exploration of past human landscapes in central Europe. Copyright © 2014 John Wiley & Sons, Ltd.